THE POWER OF LOVE: AN ANALYSIS ON MAGGIE AND BRYCE RELATIONSHIP IN NICHOLAS SPARKS’S NOVEL THE WISH - Mumpuni, Erlina Dwi; Wajiran, Wajiran (Lire Journal (Journal of Linguistics and Literature), 2024)
This research was conducted with the aim of analyzing the power of love that made Maggie continue to love Bryce until the end of her life. Even though, Bryce had passed away and chose to live alone without seeking new love. This study used qualitative research methods. The source of the data is The Wish. The supporting data are taken from a book Triangular Theory of love. The researcher sorts out data related to the power of love in the main character's relationship. Then the data are analyzed based on Robert Sternberg's theory. The results of this study show that Maggie and Bryce's relationship is included in the consummate love type because it contains three love components of the triangular theory of love: intimacy, passion, and commitment/decision. The three components of love combined create the strength of a relationship that keeps Maggie going, including love itself, memories created, and the promises made.